The Concept Of Legal Norms Of Personal Data Protection Related To Data Processing In The Form Of Artificial Intelligence - Yalid (PT. Hasba Edukasi Mandiri, 2025)
Issues examined in this study: first, How is the protection of personal data related to data processing in the form of artificial intelligence in Indonesia. Second, what is the concept of the existing legal norms of personal data protection related to data processing in the form of artificial intelligence. The method of research is carried out in literature with the type of normative legal research, according to dogmatic issues related to the emptiness of norms. Findings in this study found the protection of personal data related to data processing in the form of artificial intelligence in Indonesia there are two views. In this regard, the protection of personal data in data processing through artificial intelligence in Indonesia has no legal certainty to be protected. Because legal certainty refers to the application of clear, fixed, consistent and consequent laws whose implementation cannot be influenced by subjective circumstances. The concept of existing legal norms for personal data protection related to data processing in the form of artificial intelligence special arrangements stipulated in Law Number 27 of 2022 can be said to have accommodated personal rights. However, the existing condition of artificial intelligence norm is only legally domiciled as a legal object, because it is needed by the party responsible for the actions of artificial intelligence. Legal liability for the actions of artificial intelligence can be charged or imposed on the organizers of artificial intelligence.